De Vrije Universiteit en de organisatie van de theologie in Nederland - Vroom, Hendrik M. (Verbum et ecclesia, 1997)
Theology at the Free University of Amsterdam: the foundation in 1880 and its relation to the churches. In this second part of the description of the Dutch system of protestant theology the background of the foundation of the Vrije Universiteit at Amsterdam has been described. The foundation of the VU was a reaction on the "duplex ordo" at the state universities. All disciplines of theology have been understood to be fully theological (and not some neutral, some confessional). The views of Abraham Kuyper concerning the relation between the theological faculty and the refonned churches are discussed, and shortly also his conception of theology.